Gestão da variabilidade espacial de atributos químicos do solo com base na amostragem e taxa variável de fertilizantes e corretivos para a cultura da soja - Machado, Paulo Roberto (2019)
Precision Agriculture seeks to optimize the inputs used in the crop to improve productivity, reduce costs, reduce environmental impacts and increase work efficiency, thereby optimizing decision making. With the spatial and temporal analysis of production one can infer which factors influence it. These analyzes are carried out with the help of software to determine soil fertility, productivity. This work aims to analyze the spatial and temporal variability of soil chemical attributes and soybean yield. With the descriptive statistics of soil chemical attributes, it showed that the area is not homogeneous. Coefficient of variation values greater than 40% reflect the heterogeneity of the two years of sampling, as in the results of the analysis of the sampling years 2012 and 2017. With the classic statistics and the software Campeiro version 7.40, to do the spatial analysis (IDW), soil chemical attributes and harvest. A georeferenced sample of 100 x 100 was performed, totaling 33 points in an area of 33.83 ha. A method of visualizing the fertility and harvest maps to study the spatial and temporal variability in the agricultural areas, showing that it was sufficient to make the classes of recommendation of correctives and fertilizers.